2015
DOI: 10.1093/mnras/stv1043
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the correlation between peak episodic jet power and X-ray peak luminosity of the soft state in black hole transients

Abstract: Episodic jets are usually observed in the intermediate state of black hole transients during their X-ray outbursts. Here we report the discovery of a strong positive correlation between the peak radio power of the episodic jet P jet and the corresponding peak X-ray luminosity L x of the soft state (in Eddington units) in a complete sample of the outbursts of black hole transients observed during the RXTE era of which data are available, which follows the relation log P jet = (2.2 ± 0.3) + (1.6 ± 0.2) × log L x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 82 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…Wind and jet can be exist simultaneously e.g., in LMXBs [Drappeau et al, 2017, Homan et al, 2016, Tetarenko et al, 2018, in active galactic nuclei [e.g., Tombesi et al, 2014], and morphologically, in some systems the wind outflow geometry has been inferred to be a conical shape [e.g., Degenaar et al, 2016, Knigge et al, 1995, Tombesi et al, 2015. Moreover, we observe radio emission in all spectral state of LMXBs, the radio flux of HS is 10 to 1000 times fainter than the VHS radio flux, the jet power of VHS is positively correlated with peak X-ray luminosity of HS, and it is believe that the radio emission of VHS is due to the synchrotron process by outflowing relativistic electron near to the compact object on accretion disk [e.g., Fender et al, 2004, 1999, Fender & Hendry, 2000, Fender et al, 2009, Fender & Kuulkers, 2001, Muno et al, 2001, Rushton et al, 2012, Zhang & Yu, 2015. Recently, Motta et al [2018] have emphasized that the radio-loud/quiet nature of BH LMXBs can be an inclination effect, i.e., the low inclination source is radio loud and vice versa but it will also depends on opening angle of outflow e.g., V404 Cyg is a high inclination source and radio-loud.…”
Section: Introductionmentioning
confidence: 88%
“…Wind and jet can be exist simultaneously e.g., in LMXBs [Drappeau et al, 2017, Homan et al, 2016, Tetarenko et al, 2018, in active galactic nuclei [e.g., Tombesi et al, 2014], and morphologically, in some systems the wind outflow geometry has been inferred to be a conical shape [e.g., Degenaar et al, 2016, Knigge et al, 1995, Tombesi et al, 2015. Moreover, we observe radio emission in all spectral state of LMXBs, the radio flux of HS is 10 to 1000 times fainter than the VHS radio flux, the jet power of VHS is positively correlated with peak X-ray luminosity of HS, and it is believe that the radio emission of VHS is due to the synchrotron process by outflowing relativistic electron near to the compact object on accretion disk [e.g., Fender et al, 2004, 1999, Fender & Hendry, 2000, Fender et al, 2009, Fender & Kuulkers, 2001, Muno et al, 2001, Rushton et al, 2012, Zhang & Yu, 2015. Recently, Motta et al [2018] have emphasized that the radio-loud/quiet nature of BH LMXBs can be an inclination effect, i.e., the low inclination source is radio loud and vice versa but it will also depends on opening angle of outflow e.g., V404 Cyg is a high inclination source and radio-loud.…”
Section: Introductionmentioning
confidence: 88%
“…More importantly, they also found that the rate-of-change of the X-ray luminosity around the spectral state transition is positively correlated with both the luminosity corresponding to the hard-to-soft state transition and the peak luminosity of the outbursts. Motivated by these studies, Zhang & Yu (2015) found the peak power of the episodic jet is positively correlated with both the peak luminosity of the soft state (i.e., outburst peak luminosity) and the rate-of-change of the typical X-ray luminosity around the hard state during the rising phase of outbursts in several black hole X-ray binaries in which good measurements of source distances and black hole masses are available. This series of investigations indicates that spectral state transitions, as well as accretion or jet phenomena associated with the transitions, such as episodic jets, are driven by non-stationary accretion instead of stationary accretion.…”
Section: Introductionmentioning
confidence: 93%
“…The energetic, collimating episodic jets had been observed in active galactic nuclei, stellar binaries, and protostars. For instance, in the X-ray binaries, episodic jets are usually observed during their X-ray outbursts and intense radio fares (Fender et al 2004;Zhang & Yu 2015). Practical models and numerical simulation suggested that the episodic jets may be driven by magnetic instability in the accretion disc (Yuan et al 2009;Yuan & Zhang 2012;Zhao et al 2020).…”
Section: The Modelmentioning
confidence: 99%